Eculizumab for the acute attack of neuromyelitis optica spectrum disorder - Zhuang, Qingqing; Huang, Wenjuan; ZhangBao, Jingzi; Wang, Zhouzhou; Zhou, Lei; Li, Xiang; Fan, Yuxin; Wang, Liang; Xiao, Yiqin; Yu, Jian; Wang, Min; Tan, Hongmei; et al. (Frontiers in Immunology, 2025)
ObjectiveTo assess clinical outcomes in patients treated with eculizumab for acute attacks of aquaporin-4 antibody-positive neuromyelitis optica spectrum disorder (NMOSD).MethodsWe retrospectively analyzed prospectively collected data from the Huashan NMOSD registry cohort, and included patients who received eculizumab within 30 days of attack onset. Eculizumab was administered at 900 mg weekly for four weeks, followed by an eight-week observation period. Primary outcomes included visual acuity and visual field for optic neuritis (ON) and muscle strength, assessed using the Medical Research Council (MRC) scale for longitudinally extensive transverse myelitis (LETM). Serum neurofilament light chain (sNfL) and glial fibrillary acidic protein (sGFAP) levels were also monitored.ResultsNine patients (seven with ON, two with LETM) were included. All patients received high-dose intravenous methylprednisolone prior to eculizumab treatment. Following eculizumab, six of the seven ON patients showed significant improvements in visual acuity and visual fields, with five recovering to near-normal or pre-attack vision. Visual field mean deviation improved from −22.4 dB to −2.0 dB (p = 0.008). Among LETM patients, one regained substantial lower limb strength (MRC grade 0 to 3 proximally, 4 distally), while the other showed improvement in distal strength (MRC grade 0 to 3). Serum sGFAP decreased from 278.0 to 130 pg/mL (p = 0.027), while sNfL levels transiently increased before stabilizing. One LETM patient developed a urinary tract infection, and another had Klebsiella pneumoniae pneumonia; all infections were effectively treated.ConclusionEculizumab may yield favorable outcomes in acute NMOSD attacks, with infection monitoring being particularly important in severe cases.